Revision of the Orasema festiva species group (Hymenoptera: Chalcidoidea: Eucharitidae) - Burks, Roger A.; Mottern, Jason; Heraty, John M. (Zootaxa, 2015)
The Neotropical Orasema festiva species group is revised, retaining O. festiva (Fabricius) and O. delicatula (Walker) as valid species, and describing four new species: O. alvarengai n. sp., O. caesariata n. sp., O. erwini n. sp., and O. reburra n. sp. The festiva-group is characterized by features that are unusual or unique in Orasema, including the presence of 8–11 labral digits, a smooth face, and a lateral petiolar carina. The egg of O. caesariata and the first-instar larva of O. delicatula are newly described and found to be similar to other species of Orasema.